Effectiveness of Telemedicine and Remote Monitoring in Reducing Postpartum Hemorrhage Rates: A Meta-Analysis - Dina Anggraini; Dwie Yunita Baska; Kintan Anissa (HM Publisher, 2024)
Postpartum hemorrhage (PPH) is a leading cause of maternal morbidity and mortality worldwide, particularly in low- and middle-income countries (LMICs) with limited access to healthcare. Telemedicine and remote monitoring technologies offer potential solutions for early detection and management of PPH. This meta-analysis aimed to evaluate the effectiveness of these technologies in reducing PPH rates. A systematic search of PubMed, Embase, Cochrane Library, and Web of Science was conducted for studies published between 2013 and 2024 investigating the impact of telemedicine and remote monitoring interventions on PPH rates. Randomized controlled trials (RCTs) and observational studies with a control group were included. The primary outcome was the incidence of PPH (blood loss ≥500 ml after vaginal delivery or ≥1000 ml after cesarean delivery). Pooled risk ratios (RR) with 95% confidence intervals (CI) were calculated using a random-effects model. Publication bias was assessed using funnel plot asymmetry and Egger's test. Six studies involving 4200 women met the inclusion criteria. The pooled analysis demonstrated a statistically significant reduction in PPH rates in the intervention groups compared to the control groups (RR 0.56; 95% CI 0.47-0.67; p<0.00001). The funnel plot was symmetrical, and Egger's test was not statistically significant (p=0.45), suggesting no evidence of publication bias. Telemedicine and remote monitoring interventions are associated with a significant reduction in PPH rates. These findings support the integration of these technologies into postpartum care to improve maternal outcomes, particularly in resource-constrained settings.